Training intensity distribution analysis by race pace vs. physiological approach in world-class middle- and long-distance runners - Kenneally, M.; Casado, A.; Gomez-Ezeiza, J.; Santos-Concejero, J. (European Journal of Sport Science, 2021)
This study aimed to analyse the training intensity distribution (TID) of a group of 7 world-class middle- and long-distance runners over 50 weeks using two different approaches to organise TID zones: (1) based on individual specific race pace and; (2) based on physiological parameters. Analysed training data included training volume, intensity and frequency. The average weekly volume for the group was 135.4 ± 29.4 km·week-1. Training volumes for Z1, Z2 and Z3 were 88.5 ± 1.1%, 7.4 ± 0.8% and 4.1 ± 0.7% respectively for race-pace based approach, and 87.2 ± 1.2%, 6.1 ± 0.7% and 6.6 ± 0.9% respectively for the physiological approach. Differences were found between the approaches in Z2 (large effect, ES = 1.20) and Z3 (moderate effect, ES = 0.93). The approach based on race-pace zones produced pyramidal distributions in both middle- and long-distance runners across all phases of the season. The physiological approach produced polarised and pyramidal distributions depending of the phase of the season in the middle-distance runners, and pyramidal type TID across all phases of the season in the long-distance runners. The results of this study demonstrate that the training analysis in a world-class group of runners shows different TID when assessed relative to race pace versus to physiological zones. This highlights a potential deficiency in training analysis and prescription methods which do not make reference to specific performance. An approach which makes reference to both physiological and performance measures may allow for a more consistent and logical analysis.